2014
DOI: 10.1002/dmrr.2528
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine C‐peptide mechanism underlying INS1 beta cell adaptation to oxidative stress

Abstract: These findings demonstrate an autocrine C-peptide mechanism in which C-peptide is bioactive on INS1 beta cells exposed to stressful conditions and might function as a natural antioxidant to limit beta cell dysfunction and loss contributing to diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…Importantly, the antidiabetic sulfonylurea glibenclamide, which induces endogenous C-peptide secretion, also reversed the diazoxide increase in ROS. Similarly, extracellular potassium, which depolarizes the cells otherwise hyperpolarized by diazoxide and leads to secretion of C-peptide, caused a concentration-dependent reduction in H 2 O 2 -induced ROS to levels measured with diazoxide absent (65). These results extend previous results (10) by specifying a significant bioactivity of C-peptide directly on the ␤-cells and supports an autocrine mechanism in which C-peptide acts on INS-1 ␤-cells by lowering intracellular ROS however generated.…”
Section: E959 Physiology Of C-peptidementioning
confidence: 99%
“…Importantly, the antidiabetic sulfonylurea glibenclamide, which induces endogenous C-peptide secretion, also reversed the diazoxide increase in ROS. Similarly, extracellular potassium, which depolarizes the cells otherwise hyperpolarized by diazoxide and leads to secretion of C-peptide, caused a concentration-dependent reduction in H 2 O 2 -induced ROS to levels measured with diazoxide absent (65). These results extend previous results (10) by specifying a significant bioactivity of C-peptide directly on the ␤-cells and supports an autocrine mechanism in which C-peptide acts on INS-1 ␤-cells by lowering intracellular ROS however generated.…”
Section: E959 Physiology Of C-peptidementioning
confidence: 99%
“…The antioxidant effect of C‐peptide extended to INS‐1 β cells exposed to the model ROS compound H 2 O 2 . A key observation of the study was that INS‐1 β cells undergoing secretory blockade in the presence of the K ATP channel opener diazoxide exhibited increased ROS when challenged with H 2 O 2 and this increase was reversed by direct application of exogenous C‐peptide . Importantly, the antidiabetic sulphonylurea glibenclamide, which induces endogenous C‐peptide secretion, also reversed the diazoxide‐induced increase in ROS in INS‐1 β cells (Table ).…”
Section: C‐peptide Protects Pancreatic β Cells From Glucotoxicitymentioning
confidence: 96%
“…To start investigating whether C‐peptide has a role in decreasing cellular stress in compromised β cells, we exposed INS‐1 β cells to either 5.5 mmol L −1 (low) or 22 mmol L −1 (high) glucose in the presence or absence of C‐peptide, and evaluated apoptosis after incubation for 48 h. We observed that exposure of INS‐1 β cells to 22 mmol L −1 glucose significantly increased apoptosis compared to cells in 5.5 mmol L −1 glucose ( P < 0.005; Table ). Addition of 5 nmol L −1 C‐peptide to 22 mmol L −1 glucose‐containing medium significantly reduced apoptosis in INS‐1 β cells compared to cells in 22 mmol L −1 glucose in the absence of C‐peptide ( P < 0.005; Table ) .…”
Section: C‐peptide Protects Pancreatic β Cells From Glucotoxicitymentioning
confidence: 97%
See 2 more Smart Citations